Viability of ovine spermatozoa collected from epididymides stored at 18°-25°C for 48 hours post mortem - T.G. Bergstein-Galan (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The objectives of this study were to verify the time during which viable ovine spermatozoa could be recovered from the cauda epididymis kept at ambient temperature (18-25°C). Sperm collected in an artificial vagina (AV) were used as control. Spermatozoa samples were collected with an AV and from epididymis at 0 (G0), 6 (G6), 12 (G12), 24 (G24), and 48 (G48) hours post mortem. Total motility (TM), progressive motility (PM), hypo-osmotic membrane integrity test (HOST) and morphological changes were assessed. TM decreased (P<0.05) from 24 hours post mortem (70.0±1.9%) compared to AV (86.4±1.0%). PM decreased (P<0.05) from 12 hours after death (31.3±4.0%) compared to AV group (73.2±1.4%). The percentage of viable cells in HOST decreased (P<0.05) in the G48 (60.0±8.9%). Spermatozoa recovery was lower (P<0.05) 48 hours after death (2064.2±230.7 x 106 spermatozoa) compared to G0(2623.6±288.4 x 106 spermatozoa). In conclusion, under the conditions of this study, it would be possible to use epididymal spermatozoa recovered up to 24 hours after death for artificial insemination or in vitro fertilization; however, fertility trials are necessary to prove this hypothesis.